Single parents and child support systems an international comparison - Cook, Kay ca. 20./21. Jh; Meysen, Thomas 1967-; Byrt, Adrienne 1983- (Edward Elgar Publishing, 2024)
"Taking a novel approach to child support policy analysis, Single Parents and Child Support Systems locates the transfer of payments between separated parents within a wider social policy ecosystem and compares the political, institutional and administrative dimensions of child support policy enactment across the globe. Featuring contributions from an interdisciplinary collective of researchers in social policy, social work, sociology, economics and law, the book assesses how child support policies align conceptually with other social policies. Single Parents and Child Support Systems begins by setting out how children's and single parents' economic welfare is conceived across countries in relation to the triple burden of financial, caring and administrative responsibilities faced by single mothers. Chapters map how post-separation child support policy reinforces or breaks from the gender and family logics that underpin welfare and family policies in 10 different countries spanning corporatist, liberal and Nordic welfare regimes. Offering extensive coverage of a diverse range of international legal provisions and social policies, this stimulating book will be an essential resource for academics and researchers of social policy, social work, family law and gender studies. Its practical insights and suggested avenues for reform will also benefit policy makers, child support administrators and legal professionals"--
Literaturangaben jeweils im Anschluss an die Beiträge
Keywords: Kindergeld; Sozialhilfe; Alleinerziehender; Child support / Cross-cultural studies; Domestic relations; Social policy; Single parents; Parents uniques; Electronic books; Aufsatzsammlung